Unlocking the potential: the influence of sustainable finance solutions on the long-term sustainability of small and medium-sized enterprises - Ahmed Idi Kato; Evelyn Germinah Chiloane-Tsoka; Paddy Mugambe (Cogent Business & Management, 2024)
In recent times, there has been a global shift towards sustainable finance, aligning financial activities with environmental, social, and governance principles (ESG). This trend is crucial for promoting sustainable businesses and driving positive change, especially in East Africa where small and medium enterprises (SMEs) play a vital role in economic growth and job creation. Sustainable finance adoption within the SME sector is key to long-term economic sustainability and environmental responsibility. A mixed-methods approach was employed, utilizing the multi-regression model in SPSS 29.0 to analyze the outcomes. The multi-regression analysis of panel data from 150 private venture capital (VC) companies indicates that enhanced access to sustainable finance, proactive government engagement, and robust policy frameworks accounted for 14.7% of the observed long-term sustainability successes among SMEs. This translated to enhanced productivity and growth within the SME sector. The study carries significant policy implications. It highlights the importance of policymakers promoting and incentivizing the adoption of sustainable finance practices among SMEs. Additionally, investors who prioritize ESG factors can drive demand for sustainable finance options, supporting SMEs that prioritize sustainability. This collaboration between policymakers and investors can promote sustainable business practices, ensuring the success and resilience of SMEs while advancing overall sustainability goals. However, the study's limited scope and the nascent stage of the field may constrain the findings' applicability, underscoring the ongoing necessity to expand sustainable finance access and policy frameworks to support SMEs in their environmentally responsible strategies for enduring success and resilience
Keywords: 650; Sustainable finance; sustainability practices; SMEs sustainable growth; sustainable venture capital; sustainable productivity